Enhancing international customer–supplier relationships through IT resources: A study of Taiwanese electronics suppliers - Jean, Ruey-Jer; Sinkovics, Rudolf R; Cavusgil, S Tamer (Journal of International Business Studies, 2010)
The growing popularity of outsourcing and offshore-partnering activities raises the issue of what strategies are appropriate for firms to successfully manage customer–supplier relationships in the international context. Little has been written about how information technology (IT) systems may impact on international exchange relationships. In the present study, we report on how suppliers use IT as a strategic resource to govern their international exchange relationships with multinational enterprise customers. Taking the supplier's perspective, we propose that two types of IT resources – IT advancement and electronic integration – create value for suppliers with respect to innovativeness and market performance. We argue that this value creation process is mediated by three specific forms of governance: cooperativeness, output monitoring, and behavior monitoring. To test these arguments, primary data, obtained from 240 Taiwanese electronics suppliers, are used for hypothesis testing. The survey results provide evidence that suppliers’ IT resources enable them to work effectively with their international key customers. Importantly, of the three governance mechanisms, cooperativeness has the strongest impact on supplier performance, owing to supplier electronic integration. Post-hoc analysis revealed that cultural distance does not play a role in moderating the relationship between IT resources and governance mechanisms in international exchange.